Mathematics Achievement on Probability using The Problem Solving Process of Polya for Students Grade 6: https://doi.org/10.69692/SUJMRD080255 - VONGSIPASEUTH, Bounmor; PHOMMANITH, Khamsone; SENGALOUN , Khamsom; SILIVANH , Sommay (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research aims to comparison of Mathematics learning achievement on probability for students grade 6 after using the problem solving process of Polya with 70% achievement criterion, to comparison of Mathematics learning achievement before and after using the problem solving process of Polya, to Study teamwork and Attitude toward Mathematical for Mathematics learning after using the problem solving process of Polya on probability for students grade 6. The subjectsof this study were 30 in students grade 6 in the second semester of the 2021 academic year at Pasathipatai School Louang Prabang Province. They were randomly selected by using cluster random sampling The instruments including the Lesson Plan focus on problem solving process of Polya, thetest about learning in Mathematics, and the questionnaire about teamwork and Attitude toward Mathematical. A data analyzed by percentage, mean, standard deviation, and t-test. The result found that: Students grade 6 had Achievement in Mathematical learning on probability after using the problem solving process of Polya higher than 70% at the .05 level of significance, had Achievement in Mathematical learning on probability after using the problem solving process of Polya higher than before using the problem solving process of Polya, had teamwork and attitude toward Mathematical for Mathematics learning after using the problem solving process of Polya on probability was at a high level.